Epidemiological, Microbiological, and Clinical Characteristics of Multi-Resistant Pseudomonas aeruginosa Isolates in King Fahad Medical City, Riyadh, Saudi Arabia - Taghreed A. Hafiz; Eman A. Bin Essa; Sarah R. Alharbi; Ahmed S. Alyami; Zeina S. Alkudmani; Murad A. Mubaraki; Norah A. Alturki; Fawzia Alotaibi (Tropical Medicine and Infectious Disease, 2023)
Increasing rates of serious multi-drug resistant (MDR) Pseudomonas aeruginosa infections have been reported globally, including in Saudi Arabia. This retrospective study investigates the epidemiological, microbiological, and clinical characteristics of multi-resistant P. aeruginosa (n3579 clinical isolates) in King Fahad Medical City, Riyadh, Saudi Arabia (2019–2021). Information on antimicrobial susceptibility and medical history was collected from the hospital database. P. aeruginosa infections occurred in 55.6% of males and 44.4% of females, and P. aeruginosa was more prevalent in children than in adults. Our analysis showed that P. aeruginosa had the highest sensitivity to amikacin (92.6%) and greatest resistance to aztreonam (29.8%), imipenem (29.5%), ceftazidime (26.1%), meropenem (25.6%), and cefepime (24.3%). MDR and extensively drug resistant (XDR) strains were more prevalent in male than female patients. Female patients showed higher rates of infection with pan-drug resistant (PDR) strains. Respiratory samples contained the majority of resistant isolates. Septic shock and liver disease were strongly correlated with mortality in the ICU patient group after analysing the relative risk associated with mortality. Our study emphasises the threat of multi-resistant P. aeruginosa in Saudi Arabia (and potentially the Middle East) and highlights important sources and contexts of infection that inhibit its effective control and clinical management.